Intelligent Technology for Optimizing the Management of Order Flows of Service Systems With Imprecisely Defined and Natural Language Data - Skalozub, V. V.; Horiachkin, V. M.; Terletskyi, І. А. (Science and Transport Progress, 2023)
Purpose. The tasks of data classification and optimization of order flow management in service systems are widespread. The development of an intelligent information technology (IIT) for optimal management of order flows in service systems (OMFS&S), taking into account imprecisely defined and natural language data characteristics (IDD), implemented on the basis of a modified Hamming network (MHN), is currently relevant, scientific and practical. The main purpose of the work is to develop and improve mathematical models and procedures of the OMFS&S and the formation of IIT based on the MHN with IDD. Methodology. New formulations of the tasks of the OMFS&S, which are characterized by the IDD, are proposed. Mathematical models and intellectual procedures for optimizing the flows of OMFS&S based on MHN have been improved. Software tools for IIT based on MHN and procedures of OMFS&S processes were developed. Numerical studies of the correctness and efficiency of solutions were carried out. Findings. New task formulations of the OMFS&S according to the IDD were formed, which differ in the ability to take into account the results of the choice of controls in the previous steps. Improved mathematical models and productive intellectual procedures of the OMFS&S based on MHN were developed, and the scope of their application was analyzed. IIT software tools for the processes of OMFS&S with IDD were developed and studied, and a numerical experiment was conducted to confirm the reliability and efficiency of the proposed models and methods of OMFS&S processes. Originality. The paper improves mathematical models and productive intelligent procedures for optimizing flows based on the results of classification by MHN. Variants of models for the functioning of OMFS&S procedures have been developed, where flow elements are considered either in isolation from others, or the optimal control choice for the current element affects the maintenance of subsequent elements. Practical value. The intelligent information technology developed on the basis of modified Hamming networks allows optimizing the management of order flows in service systems with imprecisely defined and natural language data characteristics.